A Study on Comparison of Creation in the Ancient near East: Exploring Creation Myths and Religious Worldviews in the Ancient Near East (Journal of Advances and Scholarly Researches in Allied Education, 2012)
All cultures celebrate such myths and attribute to them varying degrees of literal or symbolic truth. Myths are retold orally from generation to generation and/or preserved in sacred collections or scripture, often believed to have emanated from a deity or deities. Myths are not only the stories of so-called dead cultures and religions such as those of the Ancient Greeks, Romans, Norse, or Egyptians. Extraordinary and supernatural sacred narratives are central to Christians, Jews, Muslims, Hindus, Buddhists, and Taoists, as well as to people of animist traditions to which the terms “pagan” and “primitive” have traditionally been applied with a negative connotation. Most mythologies which is to say, religions have deities, most have heroes who perform certain ritual deeds, many of which are found in most mythologies the quest, the descent to the Underworld, for example. Universal patterns or common motifs in mythology have been called archetypal, that is, reflective of psychological tendencies that are common to the human species as a whole. Nowhere in the Bible is the worldview of the ancient Israelites or their values toward nature explicitly laid out. This is not surprising. Ancient Israel was what Edward Hall has characterized as a high context society. In high context societies a rich common culture is assumed by all the members of the society, and the identity of individual members is defined in terms of that culture.